The feasibility and impact of a painted designs intervention on school children's physical activity. Issue 2 (3rd April 2023) - Wong, Janet B.; McCallum, Kyle S.; Frehlich, Levi; Bridel, William; McDonough, Meghan H.; McCormack, Gavin R.; Fox, Kris; Brunton, Laura; Yardley, Leah; Emery, Carolyn A.; Hagel, Brent
ABSTRACT: Interventions such as painted designs on school tarmacs may increase children's physical activity during school hours. This mixed-methods study examined the influence of a painted designs (e.g., traditional games, random circles) intervention on the physical activity experiences of elementary school children. Systematic observations and accelerometer data were collected to evaluate the type and quantity of student physical activity. Interviews were used to explore teacher and student experiences. Observed physical activity was not significantly different between intervention and control schools ( t(43)  = 0.22, p = 0.83), and children at the intervention schools undertook less physical activity (steps, moderate, vigorous, and combined moderate-to-vigorous activity) as compared with the control school ( t = 2.71–4.35, p < 0.05). Teachers and students commented that the painted designs were confusing but held potential for inclusiveness, physical activity, and learning. Additional resources and instruction may assist in better use of painted designs for physical activity and academic learning.